Locum physicians' professional ethos: a qualitative interview study from Germany - Sabine Salloch; Birgit Apitzsch; Maximiliane Wilkesmann; Caroline Ruiner (BMC, 2018)
Abstract Background In contrast to other countries, the appearance of locum physicians as independent contractors constitutes a rather new phenomenon in the German health care system and emerged out of a growing economization and shortage of medical staff in the hospital sector. Locums are a special type of self-employed professionals who are only temporally embedded in organisational contexts of hospitals, and this might have consequences for their professional practice. Therefore, questions arise regarding how locums perceive their ethical duties as medical professionals. Methods In this first qualitative study on German locum physicians, the locums' own perspective is complemented by the viewpoint of permanently employed physician colleagues. Eighteen semi-structured interviews were conducted in 2014 to explore the professional practice of locum physicians from both groups' perspectives with respect to doctor-patient-relationship, cooperation with colleagues and physicians' role in society. The data were analysed using qualitative content analysis, including a deductive application and an inductive development of codes. The results were related to key tenets of medical professionalism with respect to the question: how far do locums fulfil their ethical duties towards patients, colleagues and the society? Results The study indicates that although ethical requirements are met broadly, difficulties remain with respect to close doctor-patient contact and the sustainability of hiring locums as a remedy in times of staff shortage. Conclusions Further qualitative and quantitative research on locum physicians' professional practice, including patient perspectives and economic health care system analyses, is needed to better understand the ethical impact of hiring independent contractors in the hospital sector.